Neonatal Mechanical Ventilation-Early Experiences in central India - R D Dutt; Chandrakala Dutt; Ravi Ambey (International Journal of Medical Research and Review, 2014)
Introduction: This innovative technology of mechanical ventilation had been started since 1960s and reached to significant level in affluent nation but in our nation, it is in nascent stage. This is first kind of study measuring outcome of neonatal mechanical ventilation in central part of India.Methodology: Study was conducted for one year after permission from Institutional Research board at Neonatal intensive care unit (NICU), of Kamla Raja Hospital, G.R. Medical College, Gwalior (M.P.). It was a prospective observational study & statistically, SSSP-10 system was applied for study. In our study, we used time cycled, pressure limited, continuous flow ventilator (DRAGGER-8000). Out of total 1160 admission during study period over one year in our NICU, 79 newborns (6.81%) requiring mechanical ventilation were enrolled. 70 (88.60%) newborn were given SIMV mode and 9 (11.40%) were given exclusive CPAP as per their indication.Results: The overall survival rate was 48.10% (SIMV 42.85% (20 cases) and CPAP 88.88% (8 cases) respectively. The inborn babies were 35.44% (28 cases) and out born were 64.56% (51 cases) but survival was much better in inborn babies 64.28% (18 cases) compared to out born babies 39.21% (20 cases) which is statistically significant (p<0.05). Though male neonates were predominant 64.55% (51 cases), but outcome was better in female newborns 57.14% survival than Male.Conclusion: Mechanical ventilation is in evolving phase in central part of India. In hands training & experience will further improve outcome after few decades.